THE TRAINNING AND PRACTICE OF TUTORS AS RESEARCH SUPERVISORS IN ONLINE EDUCATION - Giordan, Marcelo; Massi, Luciana [UNESP] (Univ Estadual Campinas, Fac Educacao, 2018)
this article, we outline and discuss the training and practices of tutors who worked as supervisors on term papers in a specialization course on science education offered by the Sao Paulo Network of Teacher Education at Sao Paulo University. Based on the activity systems model we analyse the supervision practices together with tutor's answers to a questionnaire and identify main aspects to this analysis: 1) the supervision's autonomy, 2) the rules of the activity systems and 3) the community. According to this theoretical perspective, many elements point to the effective creation of a community of practice, which had a fundamental role in supervisor's education, and to the restructuring of basal supervising activities, such as writing and communication, in a context of online educational.
Keywords: Supervisor's Role; Tutor; Online Education; In-service training; Activity Systems